Patterns of hospital utilization in the Unified Health System in six Brazilian capitals: comparison between the year before and the first six first months of the COVID-19 pandemic - Margareth Crisóstomo Portela; Claudia Cristina de Aguiar Pereira; Sheyla Maria Lemos Lima; Carla Lourenço Tavares de Andrade; Mônica Martins (BMC, 2021)
Abstract Objective To analyze the temporal evolution of the pattern of hospital use in the context of the COVID-19 pandemic in Brazil. Methods This retrospective observational study compared hospital use and mortality in the Brazilian Unified Health System (SUS) in the first six months of the COVID-19 pandemic with the year before the onset of the pandemic in six Brazilian capitals (São Paulo, Rio de Janeiro, Manaus, Fortaleza, Recife, and Brasilia). It was based on secondary administrative data from the SUS Hospital Information System (SIH), focusing on the number of hospitalizations per fortnight, age, and gender of patients, hospital length of stay, and the proportions of surgical, elective, with the use of ICU, and resulting in death hospitalizations. It also compared the number of hospitalizations and mortality related to frequent diagnostic groups. Results A significant drop was identified in the number of hospitalizations as of March 2020, with the first peak of COVID-19 hospitalizations in five capitals recorded in May 2020. In the six capitals, we observed significant reductions in the mean number of hospitalizations per fortnight from the beginning of the pandemic. We also identified an increase in the mean age of the patients and the proportion of male patients. The proportion of surgical and elective hospitalizations dropped significantly in all capitals, while the proportion of hospitalizations with ICU use increased significantly. Significant increases in-hospital mortality were also recorded in the six capitals with the pandemic, including or excluding COVID-19 hospitalizations from the comparison. Conclusion The pandemic caused changes in the pattern of use and hospital indicators in the first six months in the cities considered, evidencing the need for attention to diseases with a hospital production altered by the COVID-19 course and health system performance problems in the face of challenges.